Management Examination of Production Functions to Increase Productivity - Henny Rakhmawati; Eni Widhajati; Nurani Nurani; Nevi Costari (Universitas 17 Agustus 1945 Surabaya, 2024)
This research aims to determine whether the implementation of the production function at the Bu Bandiyah tofu factory is in accordance with predetermined procedures, and to identify problems and improvements that can be used. The method used in this research is qualitative method. This research was conducted at the Bu Bandiyah Tofu Factory which is located in Talunkulon Village, Bandung District, Tulungagung Regency. The data sources in this research use primary and secondary data. Data collection uses observation techniques and interview techniques. Analysis of the data used in this research is by comparing the data obtained and the applicable theory. This research uses the stages of a management audit, namely preliminary audit, review of management testing and control, detailed audit, reporting. The results of the research are that the production planning process implemented at the Bu Bandiyah Tofu Factory is effective because it has been implemented according to established procedures, but because the company is still classified as a home-based business, it cannot predict production needs with certainty and production implementation is not optimal.